2022
DOI: 10.3390/pharmaceutics14020374
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-, Antimicrobial Agent-, and Analgesic-Incorporated Nanofibrous Scaffolds for the Therapy of Alveolar Clefts

Abstract: An alveolar cleft is a bone defect in the maxillary arch. Although the use of autologous iliac bone grafts to repair alveolar clefts is the preferred treatment method, donor-site morbidity remains a concern. In this study, we incorporated bone morphogenetic protein (BMP), an antimicrobial agent, and an analgesic into nanofibrous scaffolds for alveolar cleft therapy. Three-dimensional (3D) printing and coaxial electrospinning techniques were used to fabricate the scaffolds. BMP-2, ketorolac, and amoxicillin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Although autogenous bone grafting has remained the mainstream, its main drawbacks, donor site morbidity and limited bone supply, prompt clinicians to develop alternative materials that could meet the complicated clinical requirements of ABG (Kang, 2017;Francisco et al, 2021;Dissaux et al, 2022). Therefore, the appeal of BMP2 as a potential alternative is to avoid autogenous bone harvesting while preserving the osteogenic potential of the graft (da Rosa et al, 2019;Motamedian et al, 2022;Chou et al, 2022). In a recent umbrella review, Francisco et al (Francisco et al, 2021) reported that the use of BMP2 produced similar results regarding bone volume, filling and height to the standard technique of autogenous bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Although autogenous bone grafting has remained the mainstream, its main drawbacks, donor site morbidity and limited bone supply, prompt clinicians to develop alternative materials that could meet the complicated clinical requirements of ABG (Kang, 2017;Francisco et al, 2021;Dissaux et al, 2022). Therefore, the appeal of BMP2 as a potential alternative is to avoid autogenous bone harvesting while preserving the osteogenic potential of the graft (da Rosa et al, 2019;Motamedian et al, 2022;Chou et al, 2022). In a recent umbrella review, Francisco et al (Francisco et al, 2021) reported that the use of BMP2 produced similar results regarding bone volume, filling and height to the standard technique of autogenous bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…202 Bilayer membranes made with nanofibers containing PLGA mixed with ketorolac (an analgesic) and amoxicillin (an antibiotic) for the first layer, and nanofibers composed of PLGA/BMP-2 for the second layer did not enhance maxillary alveolar bone regeneration when implanted in rats. 203 5.5. Pharmacological and Natural Modulators of Signaling Pathways.…”
Section: Pharmacological Drugsmentioning
confidence: 99%
“…Authors claim that doxycycline might promote bone regeneration by attracting osteoblasts and reducing bone resorption via osteoclasts . Bilayer membranes made with nanofibers containing PLGA mixed with ketorolac (an analgesic) and amoxicillin (an antibiotic) for the first layer, and nanofibers composed of PLGA/BMP-2 for the second layer did not enhance maxillary alveolar bone regeneration when implanted in rats …”
Section: Bioactive Factors Incorporated Into Scaffolds Stimulate Cmf ...mentioning
confidence: 99%